Effect of several tooth-colored restorative materials on reinforcement of unsupported enamel - Mohammadreza Malekipour; Farzaneh Shirani; Parvin Mirzakoucheki; Samaneh Alaei; Mehran Safaei; Zahra Hashemzadeh (Isfahan University of Medical Sciences, 2012)
Introduction: Adhesive restorations properly transmit and distribute functional stresses at the bonding interface to tooth structures and have the potential to reinforce remaining weakened tooth structures after removal of extensive carious lesions. This study evaluated the effect of a number of adhesive restorative materials on reinforcing unsupported enamel. Materials and Methods: Seventy-five extracted sound maxillary premolars collected over 3 months and stored in 0.2% thymol solution received MOD cavities; the lingual cusps were reduced up to the pulp level. The specimens were divided into five groups (n=15). In group 1 (the positive control), dentinal tissue of the buccal wall was preserved. In other groups the buccal dentin was completely removed. In group 2 (the negative control), no restorative material was used to replace the lost dentin. The removed buccal dentin was replaced with composite resin, flowable composite resin and glass-ionomer in groups 3, 4 and 5, respectively. After thermocycling, the specimens were tested in an Instron universal testing machine. Data were analyzed with ANOVA and LSD test (a < 0.05). Results: The mean and standard deviations of fracture loads of the five groups were 122.97 ± 15.11, 44.71 ± 14.23, 78.32±17.58, 81.17 ± 19.53, and 85.33 ± 22.07 Newtons, respectively. One-way ANOVA revealed significant differences between the groups (p value = 0.00). There were significant differences in fracture loads between groups 1 and 2 and others (p value = 0.00). The difference in fracture loads between group 3 and 4 (p value = 0.678), groups 3 and 5 (p value = 0.344), and groups 4 and 5 (p value = 0.589) were not significant. Conclusion: It can be concluded that the three types of adhesive restorative materials in this study can reinforce unsupported enamel to a certain degree. Key words: Composite resin, Dental adhesives, Reinforcement, Tooth enamel.